Characterization based on the 56-Kda type-specific antigen gene of Orientia tsutsugamushi genotypes isolated from Leptotrombidium mites and the rodent host post-infection. - Takhampunya, R; Tippayachai, B; Promsathaporn, S; Leepitakrat, S; Monkanna, T; Schuster, A; Melendrez, M; Paris, D; Richards, A; Richardson, J (2014)
Abstract. Characterization of the 56-kDa type-specific antigen (TSA) genes of Orientia tsutsugamushi (OT) from three naturally infected, laboratory-reared mite colonies comprising three species (Leptotrombidium deliense [Ld], Leptotrombidium imphalum [Li], and Leptotrombidium chiangraiensis [Lc]) has revealed the presence of single and coexisting OT genotypes found in individual chiggers. The Karp genotype was found in all of the chiggers examined, whereas Gilliam and UT302 genotypes were only observed in combination with the Karp genotype. From analysis of these OT genotypes after transmission from chiggers to mice it was determined that with the Lc and Li mites, the OT genotype composition in the rodent spleens post-infection had not changed and therefore resembled that observed in the feeding chiggers. However, only the Karp genotype was found in rodents after feeding by Ld chiggers carrying Karp and Gilliam genotypes. The current findings reveal a complex association among the host, pathogen, and vector.